Evaluation on Safety of Non-steroidal Anti-inflammatory Drugs in a Tertiary Care Hospital in India: A Prospective Observational Study - Dey, Saborni; Kumar, Harsh; Shukla, Anand Kumar (Pharmaceutical Research - Recent Advances and Trends Vol. 4, 2024)
Background: The nonsteroidal anti-inflammatory drugs (NSAIDs) are among the most frequently used drugs to treat pain and inflammation. NSAIDs constitute the largest single group of drugs used worldwide, constituting more than 20% of all drug prescriptions. Although NSAIDs have enormous clinical use, but are not devoid of adverse drug reactions (ADRs) such as peptic ulcer, gastritis, renal, neurological reactions, etc. Therefore, this pilot study is intended to assess the incidence and pattern of ADRs of NSAIDs in a tertiary care teaching hospital. Methods: This is a prospective observational study, which was executed in the department of Orthopaedics with association of the department of Pharmacology, SIMS Medical College, Hapur, UP, India. A total of 600 Orthopaedic outpatients were enrolled in the study to observe the risk of ADRs due to NSAIDs. All the ADRs were further analysed in relation to age, sex, types of drug and its pattern, etc. The causality was analysed by using Naranjo’s Algorithm and severity was analysed by using the Hartwing and Siegel scale. Results: Out of the 600 patients with NSAID therapy, 35 patients (5.83%) experienced a total of 10 types of ADRs. The adverse drug reactions observed by the patients were gastric symptoms, headache, urticaria, oedema etc. The most frequently observed ADR was gastritis. Out of 35 patients who had ADRs, 62.86% were male and 37.14% were female. The study found that Gender and age did not show any statistical significance in relation to the occurrence of adverse drug reactions due to prescribed NSAIDs. Among all the prescribed drugs, Tab Diclofenac sodium accounted for 57.14% and Paracetamol for 11.42% of all the ADRs. According to Naranjo’s Algorithm, 62.87% of ADRs were possible’ and 37.14% were of probable type and ADRs were mostly mild in severity. Conclusion: In this study, the incidence of adverse reactions to nonsteroidal anti-inflammatory drugs was 5.83 and the most commonly implicated drug for the ADRs was Diclofenac sodium. Most of the adverse effects were mild and tolerable.